Super fast plasma streams as drivers of transient and anomalous magnetospheric dynamics - S. Savin; E. Amata; L. Zelenyi; V. Lutsenko; J. Safrankova; Z. Nemecek; N. Borodkova; J. Buechner; P. W. Daly; E. A. Kronberg; J. Blecki; V. Budaev; et al. (Annales Geophysicae, 2012)
We present multi spacecraft measurements in the magnetosheath (MSH) and in the solar wind (SW) by Interball, Cluster and Polar, demonstrating that coherent structures with magnetosonic Mach number up to 3 – Supermagnetosonic Plasma Streams (SPS) – generate transient and anomalous boundary dynamics, which may cause substantial displacements of the magnetospheric boundaries and the riddling of peripheral boundary layers. In this regard, for the first time, we describe a direct plasma penetration into the flank boundary layers, which is a candidate for being the dominant transport mechanism for disturbed MSH periods.